Directed search, wages, and nonwage amenities: Evidence from an online job board - Verónica Escudero; Hannah Liepmann; Damián Vergara (International Labour Organization (ILO), 2025)
We leverage rich data from a prominent online job board in Uruguay to assess directed search patterns in job applications, focusing on posted wages and advertised non-wage amenities. We find robust evidence of directed search based on posted wages in the cross-section, with stark heterogeneity by occupation: the wage-application correlation is driven by vacancies attached to lower-skill occupations, with applications to vacancies attached to higher-skill occupations showing no responsiveness to posted wages. By applying text analysis to the job ads, we elicit advertised non-wage amenities and find evidence of directed search based on non-wage amenities. Applications to vacancies attached to lower-skill occupations are consistent with lexicographic application preferences: amenities predict applications to these vacancies only when wages are not posted. Finally, we exploit industry-by-occupation minimum wage variation to demonstrate that the observed occupational heterogeneity in directed search patterns is supported by quasi-experimental difference-in-differences estimates of the impact of wages on job applications.
Keywords: E24; J31; J32; J62; J63; 330; Directed Search; Vacancies; Wages; Non-Wage Amenities; Minimum Wages